Caracterização dos efeitos do miriadenolídeo, um diterpeno imuno-regulatório, isolado de alomia myriadenia, sobre a eosinopoiese em cultura de medula óssea murina - Santos, Maria Carolina de Souza dos (2008)
The production of eosinophils a cell population that plays a major role in the pathogenesis of asthma is subject to complex regulation by a variety of drugs and cytokines, which influence the rates of apoptosis through changes in the endogenous generation of nitric oxide (NO) and cysteinyl-leukotrienes (Cys-LT). Cultures of murine bone-marrow, established in the presence of Interleukin-5 (IL-5), can be used to identify and characterize novel substances capable of regulating eosinophilopoiesis. In this study, we evaluated the effects of Myriadenolide, a diterpene isolated from Alomia myriadenia, on eosinophilopoiesis. Liquid bone-marrow cultures were established from inbred mice of the BALB/c, BP-2, B6-129 and CBA strains, in the presence of IL-5, alone or associated with various concentrations of Myriadenolide, as well as other drugs and inflammatory mediators. Cultures were incubated at 37º C for up to 7 days, in a humidified incubator, in an atmosphere of 5% CO2, before cells staining positive for Eosinophil Peroxidase (EPO) were enumerated. Myriadenolide significantly increased the number of EPO+ cells in the concentration range of 10-10 to 10-14 M, in all strains tested, and was effective in the presence of suboptimal IL-5 concentrations as well. However, it had no effect in the absence of IL-5, showing that Myriadenolide is a co-stimulus for eosinophilopoiesis, not a substitute for IL-5. Cultures established in the presence of Myriadenolide progressively accumulated EPO+ cells up to day 7, without evidence of decreasing activity. Myriadenolide counteracted the proapoptotic actions of Prostaglandin E2 (PGE2), protecting from apoptosis developing eosinophils. By contrast, it failed to protect these cells from apoptosis induced by NO, suggesting that its point of action is downstream from the generation of PGE2, but upstream from the generation of NO. The effects of Myriadenolide were mediated by the endogenous generation of Cys-LT, because they were blocked by the inhibitor of 5-lipoxygenase, Zyleuton, the blocker of 5-lipoxygenase activating protein, MK886, and the antagonist of the Cys-LT1R subtype, Montelukast. Myriadenolide interacted synergically with eotaxin in mice sensitized to ovalbumin, which do not respond to this chemokine in the absence of Myriadenolide, unlike nonsensitized controls. These results, taken together, show that Myriadenolide is a powerful new tool for research on eosinophilopoiesis, because: 1) it highlights the central role of Cys-LT in regulation of eosinophil production; 2) it provides an example of an unusually potent hemopoietic regulator; 3) it provides evidence that the mechanism of immune regulation of bone-marrow responses to eotaxin involves a partial, not total and irreversible, loss of responsiveness to the chemokine.